REPRESENTASI FEMINISME DALAM FILM WONDER WOMAN 1984 - Leonard Yoshua (2022)
The purpose of this research is to define the feminism contained in the female superhero film titled Wonder Woman‟ which was released in 2020 and to identify the implied meaning of feminism. This research uses qualitative and descriptive methods and analysis of Roland Barthes' symbolism. Roland Barthes's analysis of symbolism includes denotation (true meaning) and connotation (double meaning, which is born from cultural and individual experiences). And if the connotation has stuck in the community, then it will become a fairy tale. This research analysis focuses on the elements of narrative films, such as space and duration, figures, clashes, and goals. The results received from this research are the 15 filtered segments in the Wonder Woman film that have 4 feminism values. The value of feminism is obtained from the novel entitled Feminist Thought by Tong. Feminism consists of feminism in war, feminism in gathering decisions, feminism in intention, and feminism in love. Wonder Woman is a monoandrogynous woman, which is where she shows both feminine and manly personality at the same time. Charming, innocent, loving, willing to make a rival type, can fall in love like a woman in general. But at the same time also rude, can lead, can compete, can quote his own decisions and can take responsibility for the needs of the crowd like a man.